Tinjauan Yuridis Peraturan Perundang-Undangan sebagai Ratifikasi Perjanjian Internasional - Dewi Setyowati; Nurul Hudi; Levina Yustitianingtyas (Faculty of Law Hang Tuah University, 2016)
This study aims to resolve problems that arise in connection with reconsideration of regulations ratification of the treaty. Can legislation on treaty ratification An overview held back, and how the legal consequences if there is a decision on the revocation of laws on ratification of the treaty in Indonesia. In order to solve these problems need to be supported by the research in the form of legal material. Research obtained through library research (library research) in libraries. From this legal research to achieve results that provide answers to existing problems, namely that the Constitutional Court only had authority to examine the material legislation and ratification of international agreements is not authorized to cancel the treaty. And the cancellation of a law the ratification of international treaties have no direct correlation to the bond Indonesia against international agreements canceled. Thus the State can withdraw from its attachment to an international agreement if the agreement is contrary to the destination country. If a treaty is not regulated the procedure of withdrawal, it can refer to the rules stated in the Vienna Convention of 1969.